ASSA14-14-04 Transcatheter Closure of Patent Ductus Arteriosus in Children with Body Weight ≤ 8 kg. (1st December 2014) - Wang, Q; Zhu, X; Zhang, D; Cui, C; Chen, H; Han, X; Zhang, P; Hou, C; Sheng, X; Gu, J
Abstract : Background: To explore the interventional experience and safety, efficiency of transcatheter closure of patent ductus arteriosus (PDA) in children with body weight ≤8 kg. Methods: From May 2001 to August 2013, 102 children with body weight ≤8 kg were diagnosed PDA. All patients were underwent transcatheter closure and aorta descendens angiography 6 min after the closure. To observe the therapeutic efficacy, we examed X-ray, ECG and echocardiography 24 h, 1 month, 3 month and 6 month after operation. Results: In 102 patients, male 27, female 75, aged from 3 months to 2 years(0.9 ± 0.5 years), body weight from 5 to 8 kg (7.2 ± 0.9) kg.In 102 patients, there were funnel PDA 58, tubular PDA 39, window PDA 1 and irregular PDA 4. The narrowest PDA diameter of pulmonary artery side was 2∼10 (4.8 ± 1.6) mm by aortography. 25 patients used Amplatzer company PDA mushroom occluders, 5 patients used new type Amplatzer ADO-II occluders and 1 patient used Amplatzer Plug. 69 patients used domestic-made PDA mushroom occluders, 2 patients used domestic-made VSD occluders. The mushroom occluders waist diameter was from 6 to 16 mm. 87 patients mean pulmonary pressure were ≥25 mmHg and 43 patients mean pulmonary pressure were ≥50 mmHg before occlusion. The mean pulmonary pressure decreased with different extent after occlusion, which were consistent with dynamic pulmonary artery hypertention. 102 patients were all cured successfully and the closure achievement ratio was 100%. Conclusions: PDA patients with low body weight had their own specificness. Interventional therapy has its risk. However, it is still a safe methods to treat PDA if we performed the procedure with cautiousness, selected occluder appropriately and prevent the complication.